Perceived Value of Doctoral Education Among Cambodian Master’s Degree Students - Vandet Mean (International Journal of Interdisciplinary Research, 2026)
This study investigates Cambodian master’s degree students’ perceptions of the value of doctoral education and examines the influence of beliefs in ability to complete, joyfulness, usefulness, worthiness, and stress. Adopting a mixed-methods design, quantitative data from 165 respondents were analysed using SPSS 26 and SmartPLS 4, while qualitative insights were derived from 10 semi-structured interviews analysed with NVivo 15. The quantitative results showed that beliefs in ability to complete, joyfulness, and perceived usefulness had significant positive effects on perceived doctoral value, whereas worthiness and stress had no significant influence. Moderation analysis further indicated that stress did not moderate the relationships between the predictors and perceived value. Qualitative findings corroborate these results, revealing that students feel confident in their ability to complete doctoral studies, experience joy from intellectual growth and supportive learning environments, and view doctoral education as instrumental for career advancement and personal development. Although doctoral degrees are associated with respect and legitimacy, inconsistent societal recognition weakens the role of worthiness. Stress is experienced as both motivating and challenging but does not shape value perceptions. Overall, perceived doctoral value is driven primarily by self-belief, positive emotions, and practical relevance. This study contributes contextual evidence from Cambodia and offers insights for institutions seeking to attract and support future doctoral candidates.